2022
DOI: 10.1093/jac/dkac338
|View full text |Cite
|
Sign up to set email alerts
|

Pre-treatment HIV-1 drug resistance in antiretroviral therapy-naive adults in Eastern Africa: a systematic review and meta-analysis

Abstract: Background Pre-treatment HIV drug resistance (PDR) may result in increased risk of virological failure and acquisition of new resistance mutations. With recently increasing ART coverage and periodic modifications of the guidelines for HIV treatment, there is a need for an updated systematic review to assess the levels of the PDR among adults newly initiating ART in Eastern Africa. Methods We conducted a systematic search for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
4
2
0
Order By: Relevance
“…Our study con rms ndings from other PDR and ADR surveys conducted in Maputo and Tete [14] of Mozambique and several other studies in Southern and Eastern Africa reporting PDR and ADR to NNRTI that exceeds 10% [30][31][32]. Also, in our study, PDR and ADR were primarily driven by the K103N mutation which causes over 20-fold increased resistance to EFV [33] and is slower to revert than other mutations [34].…”
Section: Discussionsupporting
confidence: 89%
“…Our study con rms ndings from other PDR and ADR surveys conducted in Maputo and Tete [14] of Mozambique and several other studies in Southern and Eastern Africa reporting PDR and ADR to NNRTI that exceeds 10% [30][31][32]. Also, in our study, PDR and ADR were primarily driven by the K103N mutation which causes over 20-fold increased resistance to EFV [33] and is slower to revert than other mutations [34].…”
Section: Discussionsupporting
confidence: 89%
“…The estimated increase in NNRTI resistance among viremic pre-treatment PLHIV from 5% in survey round 15 to 10% in round 18 is consistent with a cross-sectional meta-analysis of predominantly clinic-based studies conducted in eastern Africa between 2017 and 2022 11 and with the longitudinal prevalence estimates reported in a meta-analysis of cross-sectional studies from eastern Africa. 10 Our estimated prevalence of pre-treatment NNRTI resistance is slightly less than what was observed in a recent analysis of 291 care-seeking PLHIV in Uganda, 12 which likely reflects differences in the burden of resistance between those who are, and aren’t engaged in care and highlights the value in estimates from population-based cohort studies.…”
Section: Discussionsupporting
confidence: 82%
“…10 Similarly, a systematic meta-analysis of studies conducted between 2017 and 2022 in eastern Africa estimated the pooled prevalence of pre-treatment NNRTI resistance to be 9.4%. 11 Longitudinal surveys of PLHIV who report to PEPFAR-supported clinics in Uganda, Kenya, Tanzania, and Nigeria (African Cohort Study) have further shown an increase in pre-treatment resistance from 8.8% (2013-2015) to 16.2% (2016-2019), of which most was NNRTI resistance. 12 However, aggregation of findings across populations with different access to diagnostics and treatment and different clinical guidelines, limited temporal resolution, and a focus on PLHIV who are enrolled in care limit the generalizability of prior studies and introduce uncertainty in estimates of the burden of HIV drug resistance among PLHIV.…”
Section: Introductionmentioning
confidence: 99%
“…We did not detect any mutation of clinical interest against INSTI, which supports the continued use of INSTI in the country. None or low resistance levels to INSTIs were also observed in previous studies from sub-Saharan African regions, such as East African countries (0%) 26 , Ethiopia (0%) 27 , Nigeria (0%) 28 , Cameroon (1.4%) 29 , and South Africa (2.2%) 30 , as well as in America such as in Brazil (0%) 31 and the US (1.9%) 32 , or 2.3% in Europe as reported in the MeditRes which is a consortium that includes ART-naïve patients newly diagnosed in France, Greece, Italy, Portugal, and Spain during 2018–2021 33 . On the other hand, we detected accessory mutations (L74M, T97A, Q95K, and S153A) that have little effect unless they present with other major mutations (Fig.…”
Section: Discussionsupporting
confidence: 72%